Advanced Distributed Systems 5th International School and Symposium, ISSADS 2005, Guadalajara, Mexico, January 24-28, 2005, Revised Selected Papers - Ramos, Felix F.; Lrios Rosillo, Victor; Unger, Herwig (Programming and Software Engineering,, 2005)
It is our pleasure to present the papers accepted and presented at the 5th Int- national School and Symposium on Advanced Distributed Systems (ISSADS) in this LNCS volume. The symposium was held in the city of Guadalajara,Mexico from January 24 to 28, 2005. The organization team was composed of members of CINVESTAV Guadalajara, Rostock University in Germany, the CUCEI and CUCEA campuses of Guadalajara University, and Instituto Tecnol´ ogico y de Estudios Superiores de Occidente, ITESO. The symposium is already a we- established annual meeting, at which scientists and people from the industrial ?eld meet and discuss the progress of applications and the theory of distributed systems in a forum during the last week of January. This year, more than 250 people from 3 continents attended the conference. Most of them are scientists, teachers, students and engineers from the local industry. The papers presented in the sessions of the symposium cover not only the subjects of distributed systems from the system level and applications, but also contributions from the area of theory and arti?cial intelligence concepts. These papers were selected out of more than 100 submissions. There was a selection ?lter in which each paper was evaluated by at least three members of the - ternational Program Committee, who came from research institutions of good reputation all over the world.